Determination Of Return On Assets: Analysis Of Solvency Ratio And Liquidity Ratio - Diky Paramitha; Sucipto (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
The main objective of this study is to provide an in-depth understanding of how solvency and liquidity ratios affect a company's ability to use its assets efficiently in generating profits, as well as to make useful contributions to managerial decision making and evaluation of company performance. Several indicators in the study were studied to analyze the determination of the solvency ratio consisting of (Debt to Asset Ratio and Debt to Equity Ratio) and liquidity ratio (Current Ratio) to Return on Assets (ROA) with a sample of several large industrial companies listed on the Indonesia Stock Exchange with a period of 2015 2020. Research with test analysis techniques analysis of test selection of Test models (chow, hausman and langrange multiplier), classical assumption test with Multicollinearity and Heteroscedasticity, Regression Test panel data, Correlation Test and hypothesis testing (partial / t-Test and simultaneous / F-Test). The results of research through partial tests and simultaneous tests with the main focus of industrial companies resulted in that the three variations of DAR, DER and CR had no influence on the Return on Assets of the company objects sampled.